Studi Analisis Komunikasi Interpersonal dalam Penyuluhan Pertanian: Perspektif Anggota Kelompok Tani Padi - Sarnawiyah Sarnawiyah; Suryanto Suryanto; Akmal Zainuddin (AGROVITAL : Jurnal Ilmu Pertanian, 2024)
This study aims to analyze communication patterns between extension workers and rice farmer groups in Wara Selatan District, Palopo City, South Sulawesi. This district has a rice field area of 134 hectares with 162 farmers, 6 farmer groups, and 4 extension workers. Based on initial observations, it was found that the number of farmer groups attending extension activities was low, often only represented by a few members. Information conveyed during extension does not always reach each member, and farmers rarely discuss the development of their farming businesses with extension workers. In addition, the role of extension workers as communicators, facilitators, mediators, and other roles has not been fully optimized. This study uses a quantitative descriptive method by distributing questionnaires based on interpersonal communication theory to identify communication patterns and existing obstacles. Research participants involved extension workers and members of farmer groups in Wara Selatan. The results of the study showed that there were several obstacles to communication between extension workers and farmers, especially in the aspect of the use of communication media. The communication media used by extension workers in conveying information was not yet effective and could not reach all members of the farmer group evenly. These constraints affect the flow of information and active participation of farmers in extension activities. The results of this study are expected to provide recommendations to improve the effectiveness of communication patterns between extension workers and farmer groups, as well as overcome existing obstacles to support the development of farming businesses in Wara Selatan District. Thus, the role of extension workers as facilitators and educators can be more optimal in encouraging the participation and success of rice farmer groups in the area.